Basal Forebrain Cholinergic System and Orexin Neurons: Effects on Attention - Villano, Ines; Messina, Antonietta; Valenzano, Anna; Moscatelli, Fiorenzo; Esposito, Teresa; Monda, Vincenzo; Esposito, Maria; Precenzano, Francesco; Carotenuto, Marco; Viggiano, Andrea; Chieffi, Sergio; Cibelli, Giuseppe; et al. (Frontiers in Behavioral Neuroscience, 2017)
The basal forebrain cholinergic system is considered as a major component of attentive mediator system. It could be activated by different ingoing inputs, and among them the hypothalamus represents an important source of projections and the orexin neurons, whose cell bodies are present in the lateral hypothalamus, highly contribute to these projections. Recently, the orexin-producing neurons have been considered to act in the basal forebrain promoting arousal and attention. Aim of the present review is trying to explain the putative effects of orexin-producing neurons and their projection to the basal forebrain in order to support the hypothesis that orexin system may contribute to attentional processing toward increased cell activity and cortical acetylcholine (Ach) release. Collectively, the available data seem to support this hypothesis: orexins excite cholinergic neurons increasing acetylcholine release in cerebral cortex contributing to cerebral cortical activation and prefrontal cortex associated with executive system. We have reviewed evidence suggesting that the BF may be a key target through which orexin neurons promote attention.